1995
DOI: 10.1093/clinids/20.5.1271
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Values of Antibody to Bordetella pertussis Antigens in Young German and American Men

Abstract: Pertussis is well controlled in the United States by routine childhood immunization. In contrast, this disease is endemic and epidemic in Germany because routine immunization has not been implemented. To gain information relating to the epidemiology of Bordetella pertussis infections, we examined the prevalence and magnitude of B. pertussis agglutinins and of IgG and IgA antibodies (detected by enzyme-linked immunosorbent assay) to four B. pertussis antigens--lymphocytosis-promoting factor, filamentous hemaggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
3

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 18 publications
4
28
0
3
Order By: Relevance
“…Using ELISA, the qualitative and quantitative differences between class-specific antibodies (IgA, IgE, IgG, and IgM) can be determined. In general, IgG and IgM antibodies, but not IgA antibodies, develop against vaccine antigens following primary immunization (146,332,579,757,821). Interestingly, persons who have been primed by infection respond to immunization with not just an IgG response but also an IgA response (446).…”
Section: Pathogenesis and Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…Using ELISA, the qualitative and quantitative differences between class-specific antibodies (IgA, IgE, IgG, and IgM) can be determined. In general, IgG and IgM antibodies, but not IgA antibodies, develop against vaccine antigens following primary immunization (146,332,579,757,821). Interestingly, persons who have been primed by infection respond to immunization with not just an IgG response but also an IgA response (446).…”
Section: Pathogenesis and Immunitymentioning
confidence: 99%
“…The past literature suggested that immunity after B. pertussis infection was lifelong whereas vaccine-induced immunity was relatively short lived (137,141,146,244,439,695). Extensive studies during the last 30 years document the limited duration of immunity following immunization, and additional careful review of old literature and the more recent study of pertussis in adults indicate that immunity following disease is also relatively short-lived.…”
Section: Pathogenesis and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent surveys reveal that a majority of individuals in a vaccinated population are transiently infected with the causative agent, Bordetella pertussis, and that it is widespread and endemic (4)(5)(6)(7)(8). In vaccinated populations, however, the bacterium induces a mild form of the disease that often goes undiagnosed (9)(10)(11). Although severe disease may be the greatest public health concern, undiagnosed pertussis poses an ongoing pervasive risk to very young (pre-vaccine), unvaccinated, and immune-compromised populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although severe disease may be the greatest public health concern, undiagnosed pertussis poses an ongoing pervasive risk to very young (pre-vaccine), unvaccinated, and immune-compromised populations. In fact, childhood disease predates the age at which children extensively socialize with each other and appears to commonly have as its source an adult, nonor mildly symptomatic carrier (10)(11)(12)(13)(14). The ability of B. pertussis to circulate in vaccinated and immune populations has been known clinically for years but has not been well studied experimentally.…”
Section: Introductionmentioning
confidence: 99%